Deciphering the Meaning of Child Naming in the Bugis Community of Sinjai Regency (An Anthroponymic Study) - Rahim, Abd. Rahman; Arifuddin, Arifuddin; Haslindah, Haslindah; Marwiyah, Marwiyah; Yusuf, Nurdin (Advances In Social Humanities Research, 2025)
This study investigates the shifting patterns and cultural significance of child naming practices in the Bugis community of Sinjai Regency, South Sulawesi, in response to global influences and modernization. Traditionally, Bugis names reflected social class, gender, religious values, and local wisdom. However, increased exposure to global culture, mass telecommunications, and diminishing traditional structures has triggered a deconstruction of these naming norms. This research aims to describe the structural patterns of Bugis personal names and analyze the socio-technological factors contributing to their transformation. Employing a qualitative descriptive approach, data were collected through random sampling, surveys of 100 respondents, and literature review, with analysis stages including data reduction, presentation, and conclusion drawing. The findings reveal seven distinct naming patterns—from one-word regional names to multi-word millennial formats—highlighting linguistic phenomena such as analogy, paragoge, and the Ta Marbuta process. The results show a generational shift from ethnically-rooted to religion-oriented and globally-influenced names. This study contributes to the preservation of cultural identity and anthroponymic knowledge while offering a foundation for future research on language, globalization, and identity in regional communities. It underscores the urgent need to document naming traditions to ensure intergenerational transmission of cultural values.